Maternal and perinatal outcome of Evan’s syndrome: a 5 years study in a tertiary care centre - K., Manjula S.; T., Jasmine Deva Arul Selvi; N., Vishnu Priya K. M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Evans syndrome is a rare autoimmune disorder characterized by simultaneous or sequential presence of a positive antiglobulin test, autoimmune haemolytic anemia (AIHA), and immune thrombocytopenia (ITP). It is characterised by frequent exacerbations and remissions within a chronic course. It was first described by Robert Evans in 1951. Incidence of AIHA is 1 per 75 - 80,000 and ITP is 5.5 /100000 per general adult population. Incidence of Evans syndrome is 1.8% to 10% of patients with ITP. Objective was to study the maternal and perinatal outcome of women with Evans syndrome (E). Methods: About 4 antenatal mothers were identified with Evans syndrome at St. Johns medical college and hospital, Bengaluru during the study period of 5 years from July 2013-July 2017. They were followed up during their antenatal, intra natal and postnatal period and outcomes were studied. All patients included in the study fulfilled the criteria for Evans syndrome. Results: There were 4 cases of Evans syndrome, with a total number of deliveries of 11859, during this 5 year study. Incidence was 0.09 per 1000 births. All patients presented with bleeding manifestations ranging from mucosal haemorrhage to subarachnoid haemorrhage (SAH) at the time of diagnosis. All patients were on treatment with either 1st or 2nd line of management with corticosteroids/ azathioprine. None had bleeding during pregnancy after the initiation of treatment. Patients had antenatal complications like preeclampsia 25%, IUGR 25%, oligohydraminos 50%, IUD 25%. 2 patients received platelet transfusions intrapartum. None had intrapartum or postpartum haemorrhage. There were no maternal and neonatal mortality. Conclusions: Evans syndrome in pregnancy is a rare condition and requires multi disciplinary approach involving specialists from obstetrics, neonatology, and hematology. Close maternal and fetal surveillance and management during pregnancy is essential to increase the possibility of a favourable pregnancy outcome in these women.